Pengaruh Corporate Social Responsilibity Terhadap Reputasi Bank Syariah - Aidil, Muhammad; Ramadhan, Abid; Syamsuddin, Sofyan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Corporate Social Responsibility (CSR) programs are commonly utilized by banks to strengthen their public image by fostering positive relationships with the community. These programs, especially in response to natural disasters and humanitarian crises, provide valuable opportunities for the banking sector to enhance trust and customer engagement. This study aims to investigate the impact of CSR initiatives on the reputation of Islamic banks. A quantitative research method was employed, utilizing a questionnaire distributed to customers, employees, shareholders, and other stakeholders involved in Islamic banking. The data were analyzed using SPSS version 26. The findings reveal a significant effect of CSR on the reputation of Bank Syariah Indonesia, specifically in the branches of K.C Bank Syariah and K.C.P Bank Syariah in Palopo